2018
DOI: 10.1093/cid/ciy486
|View full text |Cite
|
Sign up to set email alerts
|

Novel Orthobunyavirus Identified in the Cerebrospinal Fluid of a Ugandan Child With Severe Encephalopathy

Abstract: A Ugandan child with an unexplained encephalitis was investigated using viral metagenomics. Several sequences from all segments of a novel orthobunyavirus were found. The S-segment, used for typing, showed 41% amino acid diversity to its closest relative. The virus was named Ntwetwe virus, after the hometown of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…There has not been any other case of Ntwetwe virus from this region; hence, the case of this girl child was a rare and unique Pathogens 2020, 9,301 16 of 83 event. The study suggested that mosquitoes or an animal reservoir might be the probable source of transmission of this virus disease [74].…”
Section: Ugandamentioning
confidence: 98%
See 2 more Smart Citations
“…There has not been any other case of Ntwetwe virus from this region; hence, the case of this girl child was a rare and unique Pathogens 2020, 9,301 16 of 83 event. The study suggested that mosquitoes or an animal reservoir might be the probable source of transmission of this virus disease [74].…”
Section: Ugandamentioning
confidence: 98%
“…The patient went into a coma after two weeks of the onset of the disease. Diagnosis was carried out for the possible viral and bacterial diseases being circulated in the region but were negative [74]. Hence, cerebrospinal fluid (CSF) and plasma samples were used for viral metagenomic sequencing to investigate the possible etiological agent of the disease.…”
Section: Ugandamentioning
confidence: 99%
See 1 more Smart Citation
“…This heterogeneity is expected when a new technology emerges but we agree that the studies illustrate the significant challenges of replicability and potentially validity of the findings; an area of particular concern when applied to human health. Further publication of previously undescribed viruses isolated from CSF have since emerged [16], in keeping with an exponential trend for the identification of novel pathogens using metagenomics [17*]. Further discussion of the limitations of the emerging trend for novel or unexpected pathogens is explored later.…”
Section: Sequencingmentioning
confidence: 99%
“…In the past decade, novel orthobunyaviruses associated with human and/or livestock diseases (Iquitos virus, Itaya virus, Ntwetwe virus, and Schmallenberg virus) have been identified. Furthermore, known orthobunyaviruses have re-emerged or expanded to new geographical territories, a situation that has presented a serious economic and public health threat (Aguilar et al, 2011;Wernike and Beer, 2017;Edridge et al, 2018).…”
Section: Introductionmentioning
confidence: 99%